Enhancing the speech competence of philology students through didactic games - Juraeva, Nilufar (MMIT Proceedings, 2025)
The article explores the use of didactic games in the process of training philology students with the aim of improving their speech competence. The effectiveness of game-based methods in developing communicative skills, increasing motivation for language learning, and enhancing speech activity is substantiated. Examples of specific games used in classroom practice are provided